Pengembangan Agribisnis Terintegrasi Berbasis Komoditas Unggulan di Kawasan Transmigrasi Mutiara Kabupaten Muna - Laila Rizqy Karima; Rahma Laila Wulan Suci; Andri Pratama; Fadia Laiqa Melati; Ledya Kuswandi; Hamzah Hamzah; Rasidin Karo Karo Sitepu; Thoifatul Munawwaroh (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of transmigration areas often faces problems in determining superior commodities that have not yet considered the interrelationships between market aspects, regional potential, downstream processing, and community involvement in an integrated manner. This study aims to determine the priority of integrated agribusiness-based superior commodities in the Mutiara Transmigration Area, Muna Regency, using the Analytical Hierarchy Process (AHP) method. The research was conducted through interviews, field observations, and assessments by stakeholders consisting of farmers, agricultural extension workers, village government officials, academics, and relevant agencies. The results show that the market aspect is the primary consideration in the development of superior commodities in the transmigration area, followed by land suitability and production sustainability. Coconut is designated as the main superior commodity because it has broad market prospects and downstream processing potential through derivative products such as VCO, coconut milk, desiccated coconut, shell charcoal, cocopeat, and cocofiber. Beef cattle have the potential to be developed through meat processing and organic fertilizer based on integrated crop-livestock systems. Corn is developed as raw material for layer chicken feed to support the Free Nutritious Meal Program (MBG), while bananas are developed through home-based processing businesses such as chips and snack products. These results indicate the interrelationship between commodities in supporting an integrated regional agribusiness system. This study shows that the development of agribusiness in transmigration areas should not only focus on production but also be directed toward an integrated agribusiness system based on local potential, commodity downstream processing, and strengthening linkages between agricultural subsectors. The research findings are expected to serve as a basis for formulating policies for the development of sustainable, adaptive, and market-oriented transmigration areas.